A225 THE BOWEL CLEANSING NATIONAL INITIATIVE (BCLEAN): A HIGH-VOLUME SPLIT-DOSE POLYETHYLENE GLYCOL (PEG) PREPARATION VERSUS A LOW-VOLUME SPLIT-DOSE PEG SOLUTION. (15th March 2019) - Barkun, A N; Martel, M; Epstein, I L; Hallé, P; Hilsden, R J; James, P D; Rostom, A; Sey, M; Singh, H; Sultanian, R; Telford, J J; von Renteln, D; et al.
Abstract: Background: Bowel preparation is crucial in ensuring a high quality colonoscopy. Although split-dose regimens are superior with regards to bowel cleanliness, evidence still lacks amongst these as to how high-volume compares to low-volume solutions. Aims: The objective was to compare a polyethylene glycol (PEG) high-volume split-dosing (HighSD) to a PEG low-volume split-dosing (LowSD) bowel preparation. Methods: As part of one of a number trials in adult outpatients in 10 Canadian tertiary care hospitals, we prospectively randomized to split-dose PEG solutions of either high (2L+2L) or low volume (1L+1L) +Bisacodyl (15mg). Stratified randomization was carried out according to the timing of the colonoscopy (AM or PM), and a secondary randomization was completed according to diet allocation (clear fluid or low residue). The primary outcome was the Boston Bowel Preparation Scale (BBPS) in which an adequate bowel preparation was defined by a total score ≥6 with each of the 3 colonic segments subscores ≥2. Secondary objectives included patient willingness to repeat the preparation, withdrawal time, cecal intubation and polyp detection rate. Continuous and categorical variables were compared between groups using a t-test, or Chi-square test, respectively. Statistical significance is set at the p=0.05 level and analyses were intention-to-treat. Results: Over a 29-month period, 1157 subjects were allocated to HighSD and 1157 to LowSD; 93.3% completed the trial. Mean age was 56.2 ± 13.0 years old and 52.1% were female. Reasons for colonoscopy were 38.2% non-screening, 36.8% screening and 25.0% surveillance, with no between group imbalances. A significantly greater proportion of patients in the HighSD group exhibited adequate bowel cleanliness compared to the LowSD group (90.8% vs 88.1%, p=0.041), along with greater cecal intubation rates (97.4% vs 95.6%, p=0.023). Bowel cleanliness was independent of the time of colonoscopy (AM vs PM) or diet (clear liquid vs low residue). Willingness to repeat was significantly lower in the HighSD group (66.9% vs 91.9% respectively, p<0.001). Withdrawal time was not different between groups (8.31 ± 3.23 min versus 8.38 ± 3.46 min, respectively, P=0.74). The per-patient polypectomy rate was greater in the HighSD group (46.2% vs 41.8%, p=0.037). Conclusions: In this large randomized trial, split-dose high-volume PEG(2L+2L) improved bowel cleanliness compared to split-dose low volume PEG (1L+1L) + bisacodyl (15mg) independent of time of procedure (AM or PM) or diet (clear liquid or low residue diet), as well as cecal intubation and polypectomy rates. However, patient willingness to repeat the bowel preparation was markedly lower in the HighSD group Funding Agencies: received arm-length funding from Pendopharm Inc.